Development of an intervention to identify and address long-term participation and well-being needs of children and young people with acquired brain injuries and their families: A mixed methods study - Keetley, Rachel (2024)
Background: Acquired Brain Injury (ABI) is recognised as a significant public health issue, being the global leading cause of mortality and morbidity across all age groups. Approximately 40,000 UK children and young people (CYP) sustain an ABI every year from traumatic and non-traumatic causes. The physical, cognitive, emotional, and behavioural sequelae of ABI may continue to become evident months or years after the event, as childhood development progresses, and education and social demands increase. These can have a significant impact on the participation and well-being of CYP and their families.